Non-linear modeling of the plasma response to RMPs in ASDEX Upgrade. (30th September 2016) - Orain, F.; Hölzl, M.; Viezzer, E.; Dunne, M.; Bécoulet, M.; Cahyna, P.; Huijsmans, G.T.A.; Morales, J.; Willensdorfer, M.; Suttrop, W.; Kirk, A.; Pamela, S.; et al.
Abstract: The plasma response to resonant magnetic perturbations (RMPs) in ASDEX Upgrade is modeled with the non-linear resistive MHD code JOREK, using input profiles that match those of the experiments as closely as possible. The RMP configuration for which edge localized modes are best mitigated in experiments is related to the largest edge kink response observed near the X-point in modeling. On the edge resonant surfaces q   =   m / n, the coupling between the kink component ( m   >   nq ) and the m resonant component is found to induce the amplification of the resonant magnetic perturbation. The ergodicity and the 3D-displacement near the X-point induced by the resonant amplification can only partly explain the density pumpout observed in experiments.